Ideologiczny kontekst filmowych adaptacji dzieł literackich - "Dziadów" Adama Mickiewicza i "Ferdydurke" Witolda Gombrowicza = The ideological context of selected film adaptations of literary works - "Dziady" by Adam Mickiewicz and "Ferdydurke" by Witold Gombrowicz - Budzyła, Martyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Regardless of whether it sticks to the original or differs from it, a film adaptation always stands as a testimony to the original literary text and its specific reading. The following analysis of film versions of selected works of literature shows that movies reflect the directors? characteristic ways of seeing the world as well as take account of different political conditions and the expectations of potential viewers.
Keywords: Mickiewicz, Adam (1798-1855). Dziady; Gombrowicz, Witold (1904-1969). Ferdydurke; adaptacja filmowa